2020
DOI: 10.1002/ijfe.2366
|View full text |Cite
|
Sign up to set email alerts
|

Institutional determinants of FDI in Oman: Causality analysis framework

Abstract: This paper explores the institutional determinants of FDI in Oman and the role of FDI in enhancing Oman's economic diversification strategy. Time series data was collected for the selected institutional factors influencing FDI during the period 1996–2018. Unit root and Granger causality framework were used in the analysis. Results indicated that strong and clear property rights protection, corruption freedom, fiscal and trade freedom, cause FDI inflows in Oman, whereas business freedom had no effects. It is cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…FDI's inflow is also influenced by the social, political and institutional characteristics of a country. Studies within the socio-political and political-institutional genres have identified that political soundness, effective governing, proper regulations, voice and accountability, active start-up regulations, economic freedom, ease of doing business, government spending, improved one-stop services dedicated for international trade are the major determinants of FDI among world's emerging economies (Alam et al 2019;Contractor et al 2021;Ibrahim et al 2020;Kurtović et al 2020;Mourao 2018;Paul and Jadhav 2019;Rashid et al 2017). Numerous other studies have assessed determinants such as inflation, exchange, interest, and GDP growth rate, per capita GDP, export, import, gross national income and, external debt (Asiamah et al 2019;Gupta 2018;Hossain 2021;Ibrahim and Abdel-Gadir 2015;Jaiblai and Shenai 2019;Kishor and Singh 2015;Sabir et al 2019;Yimer 2017).…”
Section: Introductionmentioning
confidence: 99%
“…FDI's inflow is also influenced by the social, political and institutional characteristics of a country. Studies within the socio-political and political-institutional genres have identified that political soundness, effective governing, proper regulations, voice and accountability, active start-up regulations, economic freedom, ease of doing business, government spending, improved one-stop services dedicated for international trade are the major determinants of FDI among world's emerging economies (Alam et al 2019;Contractor et al 2021;Ibrahim et al 2020;Kurtović et al 2020;Mourao 2018;Paul and Jadhav 2019;Rashid et al 2017). Numerous other studies have assessed determinants such as inflation, exchange, interest, and GDP growth rate, per capita GDP, export, import, gross national income and, external debt (Asiamah et al 2019;Gupta 2018;Hossain 2021;Ibrahim and Abdel-Gadir 2015;Jaiblai and Shenai 2019;Kishor and Singh 2015;Sabir et al 2019;Yimer 2017).…”
Section: Introductionmentioning
confidence: 99%